2005
DOI: 10.1021/ma049005x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Vinylidene Fluoride in Supercritical Carbon Dioxide:  Effects of Poly(dimethylsiloxane) Macromonomer on Molecular Weight and Morphology of Poly(vinylidene fluoride)

Abstract: The batch homopolymerization of vinylidene fluoride (VDF) in supercritical carbon dioxide (scCO2) was studied using diethyl peroxydicarbonate (DEPDC) as a free radical initiator. Experiments were carried out to investigate the effects of monomer concentration, initiator concentration, and agitation. It was shown that poly(dimethylsiloxane) monomethacrylate (PDMS-ma) acts effectively as a stabilizer influencing both the morphology and the molecular weight of the poly(vinylidene fluoride) (PVDF) product. Scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…The H-H defect units appear at the chemical shifts -113 ppm and 116 ppm (peaks D and E in Figure 1). The H-H defect concentrations of typical commercial PVDF varies 3~6% [14]. The value of the sc-PVDFs are about 4.0%, and that of ordinary PVDF (o-PVDF) obtained from the emulsion polymerization is 5.6% (Table 1).…”
Section: -H-h Defect Concentration Of Sc-pvdfsmentioning
confidence: 98%
See 1 more Smart Citation
“…The H-H defect units appear at the chemical shifts -113 ppm and 116 ppm (peaks D and E in Figure 1). The H-H defect concentrations of typical commercial PVDF varies 3~6% [14]. The value of the sc-PVDFs are about 4.0%, and that of ordinary PVDF (o-PVDF) obtained from the emulsion polymerization is 5.6% (Table 1).…”
Section: -H-h Defect Concentration Of Sc-pvdfsmentioning
confidence: 98%
“…They set up an extended homogeneous kinetic model predicting the polydispersities of PVDF reasonably well [10]. Very recently, Howdle et al have studied the effects of stabilizers on dispersion polymerization of VDF in sc-CO 2 and obtained high molecular weight products with well-defined and uniform spherical particles [14][15][16]. However, the influence of sc-CO 2 on the crystallization behaviors of PVDF has never been investigated up to now.…”
Section: Introductionmentioning
confidence: 99%
“…At Nottingham, free-radical dispersion polymerizations in scCO 2 were investigated with the focus on developing a variety of stabilizers [38][39][40][41][42]. The synthesis of biomaterials in scCO 2 has drawn our particular attention.…”
Section: Synthesis Of Novel Block Copolymers In Sccomentioning
confidence: 99%
“…Polymerisations were carried out in a 60 ml stainless steel autoclave [24] at 55 8C, with stirring at 100 rpm, an initial vessel pressure of 4000 psi (27.21 MPa), concentration of VDF monomer [M] as 9.8 mol/l, concentration of initiator [I] as 1.5 mmol/l, and concentration of stabiliser [S] as 0.52 wt% (weight/weight relative to VDF monomer). In all cases, the reactions were deliberately terminated when the pressure in the autoclave fell by 300 psi (2.04 MPa); the point at which we found that the solid contents in autoclave approaches ca.…”
Section: Polymerisations Of Vdf In Sccomentioning
confidence: 99%
“…A tacky solid copolymer was obtained while the copolymer contained less than 23 mol% VDF. We have reported elsewhere that commercially available PDMS monomethacrylate (PDMSma) has a clear effect on the homopolymerisation of VDF in scCO 2 , leading to a high molecular weight product with a broad molecular weight distribution (MWD), and primary particles (200-500 nm) that coagulate to form larger uniform coarse particles (200-500 mm) [24]. Recently, we reported that a fluorinated graft poly(methyl vinyl ether-alt-maleic anhydride) (F-g-PMVE-MA) was an effective stabiliser for the polymerisation of VDF in scCO 2 [25].…”
Section: Introductionmentioning
confidence: 99%